THE RELATIONSHIP BETWEEN ADOLESCENTS' PHYSICAL INACTIVITY AND HEALTH - Strazdienė, Neringa; Adaškevičienė, Eugenija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
he research aim is to reveal the interrelationship between adolescents' sedentary lifestyle, physical inactivity, and health. The research methods include analysis of scientific literature, questionnaire survey, and mathematical statistical analysis of quantitative data. 528 schoolchildren (aged 13 to 14 years) and 520 parents participated in our survey. Most of the adolescents indicated being healthy or completely healthy, however, about half of the children had some health complaints over the last six months: headache, nervous tension, insomnia, dizziness, or weakness. The adolescents' indispositions could be related to the learning load and long periods of sitting, and especially insufficient physical activity in the fresh air. Nearly half of the parent respondents believed their children did not have enough time due to heavy learning loads at school and at home.  The majority of the parents indicated that their children spent a lot of time at the computer. The schoolchildren respondents who attended additional private lessons and non-formal education activities were characterised by a higher level of inactivity. Adolescents' physical inactivity is related to the time spent on ICT (computers, TV), the frequency of their choice, and the duration of doing their homework.